Influência do teor de diferentes tipos de fibras de aço em concretos autoadensáveis - Shimosaka, Tobias Jun (2016)
The use of concrete structures is fairly high throughout the world. However, conventional concrete can present problems related to the durability of the structure, as in the case of concrete voids. The concrete self compacting concrete (CAA), has been characterized as an evolution of conventional concrete, for advantages like ability to fill spaces through self adensabilidade eliminates concreting failures and enables more durable structures. Despite these improvements in the plastic state, in the hardened state, CAA characteristics closely resembling those of a conventional concrete, i.e., good compressive strength but low tensile strength and fatigue. Thus, in order to mitigate these limitations, we have to progress the use of reinforced concrete with fibers (CRF), which by the interference of the fiber acting as sewing in these cracks, result in composites with better performance against these efforts. In this context, the present study examined the self compacting concrete performance with the incorporation of steel fibers, so as a result, it was possible to keep all the improvements gained in the hardened state in their mechanical properties, without the self characteristics were lost adensabilidade CAA Thus, blends were produced with different types of steel fibers (anchored, and corrugated line), with different levels for each type (0.4%, 0.8%, 1.2% and 1.5% by volume ) and a mixture control (without fibers) and then to assess the CAA behavior when incorporated different types of fibers with different contents. The evaluation of this behavior occurred both in the plastic concrete state, as in the hardened state. For the characteristics in the plastic state, the scattering assays were performed, t500 and J. ring for the properties in the hardened state were performed resistance tests compressive, tensile strength by diametrical compression modulus. Furthermore, it sought to associate the fatigue strength of concrete, through a non-standardized assay. Aiming to analyze the transition zone, there was the scanning electron microscopy test. To analyze the results, employment was necessary statistical analysis, which evaluated the significance of the results. The results show that it was possible to maintain the characteristic of self adensabilidade CAA for all levels of employees fibers, and still obtain gains less significant compressive strength and modulus of elasticity, however, satisfactory results in tensile strength and fatigue.